A formação do professor alfabetizador de crianças com deficiência na rede pública estadual de ensino de Santa Catarina - Mendes, Rita de Cássia Cardoso (2017)
The aim of this dissertation is to understand the initial and continuous training of teachers working in the literacy cycle: 1st, 2nd and 3rd year of Elementary School, with children with disabilities, and Global Developmental Disorders - TGD, in public schools of Regional Management of Education - GERED de Tubarão, organ linked to the State Secretariat of Education - SED, in the state of Santa Catarina. It is a bibliographical, documentary and empirical study of an analytic-interpretative nature. Through the application of a questionnaire to teachers of the 1st, 2nd and 3rd years of Elementary School, through Google Forms, teachers were able to answer questions related to their education. In addition to the application of the electronic questionnaire, we adopted another data collection procedure, the SISGESC online system - an electronic school management system that SED uses for information related to the profile of its teachers and students. This research made possible the reflection about the policy of teacher training to act in the literacy of children with disabilities in the public schools of Santa Catarina, specifically the GERED of Tubarão. The analysis allowed us to conclude that, even with initial and continuing training in the area of activity, most of them are not always sufficient and meet the demands of the literacy cycle to literate all children up to eight years of age, especially children with disabilities and / or TGD. The PNAIC training, which deals exclusively with literacy and literacy training for children in the literacy cycle in an inclusive perspective, was unable to reach most of the teachers in the 1st, 2nd and 3rd year of Elementary School in the GERED schools in Tubarão. In a deeper analysis of the SISGESC system, on the Second Teachers, Bilingual Teachers and Interpreter Teachers in Santa Catarina, the state public network currently has a total of 5,469 teachers hired, mostly ACT, to work in the area of Special Education, in the attendance of 13,377 students with disabilities and / or TGD enrolled in 959 school units. Only in Tubarão's GERED, composed of 40 school units, there are 158 Second Teachers, 08 Bilingual Teachers and 03 Teacher Interpreters. Of these, only a Second Teacher is effective. The other teachers are ACT. In the field of training, the majority of teachers in the literacy cycle (62.5%) have a degree in Pedagogy, with completion between 2006 and 2018. Postgraduates (62.5%) in the Specialization modality (62.5% %), held in the period from 2010 to 2016. Graduation and Post-Graduation were funded with own resources (71.4%), and in the areas of expertise, the following emerged: Special Education; Pedagogical Knowledge and Practices of Early Childhood Education, Elementary and Special Education; and, Institutional Psychopedagogy. The data also revealed the fragility of the State of SC regarding issues related to the lack of public tenders for literacy teachers and professionals working in the area of inclusion, as well as the lack of provision of Undergraduate, Graduate and Advanced Courses , free, for the areas of Literacy, Literacy and Inclusion.